Adult humour in advertisement: a semiotic study of don’t aviation and mint video - Gemilang Bayu Ragil Saputra; Edi Santoso (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Humour was and is commonly used as a creative means in advertisements. Adult humour specifically commonly used in mature focused products advertisements or in a restrictive timeslot. Don’t Aviation and Mint itself was an advertisement for both an alcohol beverages and mobile phone services with plenty of sexual innuendos that uploaded in Ryan Reynolds’ Youtube channel in which could be accessed even in restricted mode of Youtube. Thus, this study aims to (1) analyse the Don’t Aviation and Mint video for semiotic patterns and (2) elaborate how humour is used in the aforementioned video. It was carried out using a descriptive qualitative approach with semiotic analysis based on the Saussure model of sign. The narrative analysis of the signs unravels the use of humour as an explanatory tool, creative ways in structuring the advertisement and inciting audiences’ attraction. This study also shows that Don’t Aviation and Mint used adult humour in various ways in both monologue and visual aspects. The adult humour itself was presented with varying degree of clarity through farce, slangs, a swear word and emojis.